PERANCANGAN HOTEL RESORT PEMANDIAN AIR PANAS BRUMBUN LAMONGAN TEMA ARSITEKTUR TRADISIONAL TROPIS - M. Mukhdif Al-Afghoni; Moh. Tsalis zakki (DEARSIP : Journal of Architecture and Civil, 2023)
brumbun hot spring is one of the tourist areas in Lamongan district which has a beautiful and interesting place to be developed further. The design object is a resort hotel that aims to support natural and cultural tourism in Brumbun hot springs, Lamongan. Availability of supporting facilities, namely lodging in the form of cootage classification for tourists and users who need a place to rest or stay overnight. In starting the process of a design design, a design design method is needed which is useful for making a defined and systematic design. With this method a rational and realist analysis will be carried out. The data collection process is a stage in the search for data supporting themes and objects in order to simplify the design process. In this process there are two categories of primary data collection or secondary data, as for the explanation of the data collection categories.